FORMULATION AND TEST OF ANTIBACTERIAL ACTIVITY OF PURIFICATION EXTRACT OF MUTMETE SEED (Myristica fragrans) AGAINST STREPTOCOCCUS MUTANS - Dewi Rosmalia; Minarni Minarni (Lembaga Pengembangan Kinerja Dosen, 2022)
Streptococcus mutans naturally occurs in the human oral cavity, is a microorganism that plays an important role in the initiation of dental caries. One of the efforts to prevent dental caries is the use of natural ingredients that contain antibacterial substances that can interfere with the growth or kill bacteria. Nutmeg is a natural ingredient that has antibacterial properties. Bioactive compounds in nutmeg seeds have antibacterial properties. This research aimed to determine the formulation and concentration of nutmeg seed extract which has antibacterial activity against Streptococcus mutans. The type of research used is a laboratory experiment with a post test only group design. The treatment group used purified extract of nutmeg seeds with concentrations of 25%, 20%, 15%, 10%, 7.5%, 5.0%, 2.5%, 1.25%, the positive control group used mouthwash I, T and L. The test was carried out three repetitions at each concentration, then the inhibition zone was measured using the well diffusion method. Antibacterial activity testing was carried out using the well method, the data were analyzed using the Shapiro-Wilk test, the Levene test, the one way annova test and the PST hock test. Obtained the average inhibition of nutmeg seeds against Streptococcus mutans at a concentration of 25% (18.33 mm). 20% concentration (17.16 mm), 15% concentration (16.16 mm), 10% concentration (14.66 mm), 7.5% concentration (13.33 mm), 5% concentration (6.66 mm ), the concentration of 2.5% (2.6 mm) and the smallest concentration of 1.25% had no inhibition (0 mm), while in the control group I (4 mm), T (3 mm) and L (2 mm). The higher the concentration of purified extract of nutmeg seeds, the higher the antibacterial activity against Streptococcus mutans. further research on the concentration of nutmeg seed extract preparations was carried out in vivo tests on experimental animals in order to obtain purified extract preparations of nutmeg seeds that are safe and can be an alternative choice in maintaining oral health.